2017
DOI: 10.1161/strokeaha.117.019020
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Web (Intimal Fibromuscular Dysplasia) Has High Stroke Recurrence Risk and Is Amenable to Stenting

Abstract: Carotid web is associated with high recurrent stroke/TIA risk, despite antithrombotic use, and is amenable to carotid stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
208
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(231 citation statements)
references
References 15 publications
13
208
4
2
Order By: Relevance
“…Meanwhile, patients who were treated with antiplatelet therapy had a stroke recurrence rate of 30% at 2 years. In a series of 24 patients with stroke or transient ischemic attack, Haussen et al [8] found a recurrence rate of 32%, with 16 patients undergoing stent placement across the web with no complications or recurrent ischemic events. Similarly, in a series of 5 patients with carotid webs and recurrent stroke on medical therapy, 4 patients who underwent endarterectomy were stroke free after 3–7 months of follow-up [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, patients who were treated with antiplatelet therapy had a stroke recurrence rate of 30% at 2 years. In a series of 24 patients with stroke or transient ischemic attack, Haussen et al [8] found a recurrence rate of 32%, with 16 patients undergoing stent placement across the web with no complications or recurrent ischemic events. Similarly, in a series of 5 patients with carotid webs and recurrent stroke on medical therapy, 4 patients who underwent endarterectomy were stroke free after 3–7 months of follow-up [1].…”
Section: Discussionmentioning
confidence: 99%
“…Four case series and case reports with a total of 21 patients have reported outcomes of carotid web stenting in patients with symptomatic lesions (Table 1) [4, 8-10]. The largest study to date included 16 patients [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with surgical excision has been performed with encouraging results [1,2]. Carotid artery stenting (CAS) for CaW has been rarely described [3][4][5][6]. We aim to report a multicenter experience of CAS in patients with symptomatic CaW, discuss technical features, and describe procedural and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…CW is thought to represent an intimal variant of fibromuscular dysplasia. 1,2 Although data are scarce, CW may be associated with increased stroke risk in young patients with cryptogenic anterior circulation infarction and with a high risk of stroke recurrence. 2 …”
mentioning
confidence: 99%